Development on Warehouse Layout for Order-Picking Process Improvement. A case study: Spare parts Warehouse of Company R - พฤกษารยางกุล, ปิยชาติ; ศุขหมอก, จักรินทร์ (Journal of Applied Statistics and Information Technology, 2016)
The research aims to develop the warehouse layout affected to order-picking process enhancement. The main purpose of case study on spare parts warehouse of company R is to reduce the lead-time of order-picking process which tends to be increased serving the growing demand from customers and the warehouse expansion project in the near future. Researcher applied the concept of Fast-pick area, one of essential warehouse management policies to manage the goods with high-frequency of demand. The analyzed data has been collected from the historical withdrawal from April 2014 to March 2015 under the application of inventory policy (R, s, S) for restocking transaction of this stated area. The analysis result reveals that 167 items of goods stored into Fast-pick area could be efficiently reduced its order-picking time at 43,168.69 minutes or 719.48 hours and earning the labor cost’s reduction for 82,892.25 baht during April 2015 to September 2015.